PENGARUH BEBERAPA JENIS SERBUK TUMBUHAN TERHADAP PERKEMBANGAN POPULASI KUTU BERAS SITOPHILUS ORYZAE L. DAN PERSENTASE KERUSAKAN BERAS - Risdayani Risdayani; Samharinto Samharinto; Rodinah Rodinah (Agroekotek View, 2021)
A study entitled the effect of several types of growing powder on the population development of Sitophilus oryzae L.rice lice population and the percentage of rice damage. This research was conducted for three months and carried out by the Entomology Laboratory, Faculty of Agriculture, Lambung Mangkurat University. This study used a single factor completely randomized design consisting of five treatments, namely: A (control), B (30 g chilli powder), C (30 g neem leaf powder), D (30 g babandotan leaf powder), E (30 g kencur rhizome powder). Repeated four times so that there are 20 experimental units. The observations were made in the form of the development of S oryzae and the percentage of damage to rice. The result of the experiment treatment did not show any differences between each treatment.